The Role of the Social Service in Empowering Street Children Through the Halfway House Program - Murni Latifah; Iswadi Iswadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is the role of the Indragiri Hilir Regency Social Service in empowering street children through the Baiturrahman Shelter House program, where the empowerment process does not occur in the shelter that is aimed at street children, but is aimed at underprivileged people who are outside place to stay temporarily if one of their family is hospitalized. The type of research used is field research with qualitative research methods. This research was conducted at the Indragiri Hilir Regency Social Service office using interview instruments, documentation using cellphone media, books and pens. In this study, the data sources obtained were primary data sources and secondary data. While the data analysis technique used was data reduction, presentation and conclusion drawing and to check the validity of the data, the researchers used source triangulation and technical triangulation and time. Based on the research findings, the authors found that the Baiturrahman shelter program was not focused on street children, but for underprivileged people who are outside the area for temporary stays. If one of their family members is hospitalized, they may stay temporarily at home. the stopover was for three days by bringing a number of requirements such as a family card (kk), a statement of incapacity (SKTM) and a statement letter to be cared for for a sick family member from the hospital. Regarding shelters for street children, they are only opened as a form of service, such as if the street children are caught in a raid by the Satpol PP, then the child will be taken to the Baiturrahman shelter to be given advice and the child's parents will be called to pick up their child at the halfway house, not only that the Office of Social Affairs also works with related OPDs to deal with the problem of street children. The Indragiri Hilir Regency Social Service also provided assistance in the form of groceries to the underprivileged and for street children and for street children who did not have clothes and footwear, the Social Service also provided assistance in the form of clothing and footwear for these street children.